THE EFFICIENCY OF LARGE AND MEDIUM SCALE OF THE FOOD AND BEVERAGE INDUSTRIAL PRODUCTION IN EAST JAVA: DATA ENVELOPMENT ANALYSIS (DEA) AND STOCHASTIC FRONTIER ANALYSIS (SFA) APPROACHES - Shochrul Rohmatul Ajija; Mohammad Zeqi Yasin; Jarita Duasa (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2018)
This study aims to estimate the technical efficiency of food and beverage industry in East Java in 2011 to 2013 using micro data at the company level. Stochastic Frontier Analysis (SFA) and Data Envelopment Analysis (DEA) are used to estimate technical efficiency. The output variable was the value of production, while input variables were capital, labor, raw material, and energy. The Likelihood Ratio test dictates that the Translog production function is more appropriate for use in this study. The estimation results show that the efficiency of food and beverage companies in East Java by using SFA has decreased significantly by 3.02%, whereas with the DEA method, the average technical efficiency has increased by 0.583% compared to the beginning of the year in 2011. In addition, there is difference in the efficiency value between SFA and DEA. The technical efficiency value of SFA calculation is greater than that of DEA. The dissimilarity is caused by the difference of specification in both methods related to the interaction between uncaptured variables in the DEA method. The results of this policy have implications on the government's obligation to pay attention to the food and beverage industry in order to suppress the company’ various operating costs, such as maintenance for old machines, which has an impact on on technical efficiency or improve the ability of labor in terms of machinery utilization. Therefore, in the following year, the performance of the food and beverage industry as the largest sub-sector in manufacturing is able to show the progress.